2008
DOI: 10.1038/emboj.2008.96
|View full text |Cite
|
Sign up to set email alerts
|

pVHL and PTEN tumour suppressor proteins cooperatively suppress kidney cyst formation

Abstract: In patients with von Hippel-Lindau (VHL) disease, renal cysts and clear cell renal cell carcinoma (ccRCC) arise from renal tubular epithelial cells containing biallelic inactivation of the VHL tumour suppressor gene. However, it is presumed that formation of renal cysts and their conversion to ccRCC involve additional genetic changes at other loci. Here, we show that cystic lesions in the kidneys of patients with VHL disease also demonstrate activation of the phosphatidylinositol-3-kinase (PI3K) pathway. Strik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
150
1
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 141 publications
(165 citation statements)
references
References 32 publications
12
150
1
2
Order By: Relevance
“…Previous studies demonstrated that inactivation of Vhl in proximal tubules can result in renal cyst development in aged mice 35 or after combined deletion of the tumor suppressor PTEN. 36 TAL-restricted Vhl inactivation in our study did not lead to renal cysts or renal cell carcinomas in mice up to an age of 18 months.…”
Section: Vhl Inactivation In the Tal Does Not Alter Renal Morphologysupporting
confidence: 41%
“…Previous studies demonstrated that inactivation of Vhl in proximal tubules can result in renal cyst development in aged mice 35 or after combined deletion of the tumor suppressor PTEN. 36 TAL-restricted Vhl inactivation in our study did not lead to renal cysts or renal cell carcinomas in mice up to an age of 18 months.…”
Section: Vhl Inactivation In the Tal Does Not Alter Renal Morphologysupporting
confidence: 41%
“…This observation has remained an enigma since this report by Gnarra et al (27) was published in 1997. Vhl −/− mice die during gestation (27), but simultaneous inactivation of both Vhl alleles in kidney epithelial cells similarly failed to induce renal tumorigenesis (28)(29)(30)(31). These experiments are confounded by lack of knowledge about the cell type of origin of ccRCC and restricted Cre expression (28-31); however, as we show, even when Vhl is inactivated in multipotent NPCs, Vhl loss is insufficient for renal tumorigenesis.…”
Section: Discussionmentioning
confidence: 85%
“…Deletion of Vhlh in pancreatic islets of Rip2-Cre; Vhlh fl/fl mice (hereafter referred to as Vhlh −/− ) was confirmed by PCR-mediated detection of the recombined Vhlh allele, as identical sized bands were generated by these PCR reactions as from kidney DNA derived from a kidneyspecific Vhlh −/− mouse model ( Fig. 1C; Frew et al 2008). Immunohistochemical analysis of islets of 26-wk-old Vhlh −/− mice revealed strong nuclear accumulation of HIF1␣ (Fig.…”
Section: Deletion Of Vhlh Leads To the Accumulation Of Transcriptionamentioning
confidence: 91%
“…As insulin secretion from ␤ cells is dependent on a rise in cellular ATP levels generated by glucose-stimulated ) was compared with kidney DNA of a kidney-specific Vhlh −/− mouse model (positive control: C Vhlh −/− ; negative control: C Vhlh fl/wt ) (Frew et al 2008). (D) IHC using pancreatic sections of control mice and conditional Vhlh −/− mice (bar, 100 µm; n = 3 mice).…”
Section: Vhlh-deficient Mice Display Impaired Glucose Tolerancementioning
confidence: 99%